A CeO2-modified multilayer shell-like Fe-CoS nanosheet array, its preparation method and application
Patent Information
- Application Number
- CN202311809824.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-26
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-12-26
AI Technical Summary
[0003]硫化钴是一种理想的电极材料,但其应用仍然受制于电子传输效率降低、容量衰减的问题
[0019](1)制备多层壳状Fe-CoS纳米片所需的原料成本低,合成工艺简单。Fe-CoS纳米片阵列材料本身导电性优良,氧化还原反应丰富,其多层壳的内部结构能够很好的适应反应中的体积膨胀问题,暴露了更丰富的活性位点;Fe-CoS经过CeO2的修饰,可以在保持原电极材料总体结构以及活性位点状态的情况下,增加氧化还原反应位点,进行电子结构调制,缩短离子扩散路径,增强不同组分的协同效应,进一步提升电极材料的储能效果。因此,可实现材料在比电容和倍率性能等多方面的提升。
Smart Images

Figure CN117637359B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the interdisciplinary field of nanomaterial preparation methods and electrochemical applications, specifically relating to a CeO2-modified multilayer shell-like Fe-CoS nanosheet array, its preparation method, and its application. Background Technology
[0002] Supercapacitors, characterized by high power density, fast charging and discharging speeds, and safety, are increasingly attracting the attention of researchers and playing a crucial role in the efficient utilization of green and renewable energy. Electrode materials are a key factor affecting supercapacitor performance, making the development and discovery of promising electrode materials particularly important for improving the energy density of supercapacitors.
[0003] Cobalt sulfide is an ideal electrode material, but its application is still limited by reduced electron transport efficiency and capacity decay. Recent studies have shown that, on the one hand, porous micro / nanostructures can be constructed using metal-organic frameworks (MOFs) as templates to increase specific surface area and active sites; on the other hand, transition metal doping can modulate the electronic structure, improving the conductivity of the electrode material and increasing redox reaction sites. Furthermore, modification with rare-earth metal oxides can further mitigate the structural changes that occur during electrochemical reactions. Therefore, through the design of nanoscale structures, modulation of electronic structure, and the synergistic effect of different components, high energy storage performance of electrode materials can be achieved. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention employs a simple and low-cost preparation method to fabricate a CeO2-modified multilayer shell-shaped Fe-CoS nanosheet array. First, using zeolite imidazole ester (Co-ZIF) as a precursor, a multilayer shell structure is obtained through ferrous metal doping and subsequent sulfidation steps, increasing active sites and improving material stability; the bimetallic synergistic effect simultaneously enhances conductivity and increases energy storage capacity. Second, while retaining the advantages of the original multilayer shell-shaped Fe-CoS nanosheet array, the simple modification with CeO2 further improves the energy storage performance and stability of the electrode material. Finally, growing the electrode material on a directly conductive substrate significantly improves its conductivity and stability. Therefore, the CeO2-modified multilayer shell-shaped Fe-CoS nanosheet array is widely applicable in the field of supercapacitors and is an ideal electrode material.
[0005] This invention provides a method for preparing a CeO2-modified multilayer shell-like Fe-CoS nanosheet array, comprising the following steps:
[0006] (1) Dissolve cobalt salt and 2-methylimidazole in deionized water to obtain a reaction solution. Place the cleaned nickel foam in the reaction solution and react at room temperature for 4 hours. After washing with distilled water, dry it in a forced-air drying oven to obtain Co-ZIF.
[0007] (2) Co-ZIF was placed in an aqueous solution of potassium ferrocyanide and subjected to ion exchange reaction at room temperature to obtain Fe-CoPBA nanosheet array;
[0008] (3) The Fe-Co PBA nanosheet array was placed in a sulfur source solution for sulfurization reaction to obtain a multilayer shell-shaped Fe-CoS nanosheet array;
[0009] (4) Dissolve hexamethylenetetramine and cerium nitrate hexahydrate in 40 mL of anhydrous ethanol, and then immerse the Fe-CoS nanosheet array prepared in step (3) into the above solution to react and obtain a CeO2-modified multilayer shell Fe-CoS nanosheet array, referred to as Fe-CoS / CeO2.
[0010] In step (1), the type of cobalt salt is not limited, including cobalt chloride, cobalt nitrate, cobalt acetate, etc., but the most preferred is cobalt nitrate hexahydrate.
[0011] In step (1), the molar ratio of cobalt nitrate hexahydrate and 2-methylimidazole is (1-3):(7-10), but the optimal ratio is 3:8.
[0012] In step (1), the volume of deionized water used is 25-100 mL, but the most preferred volume is 40 mL.
[0013] In step (2), the solubility of potassium ferrocyanide is 1 to 10 g / L, but the most preferred is 5 g / L.
[0014] In step (2), the ion exchange time is 0.5 to 4 hours, but the most preferred time is 1 hour.
[0015] In step (3), the type of sulfur source is not limited, including one or more of sodium sulfide, thiourea, and thioacetamide, but thioacetamide is the most preferred.
[0016] In step (3), the vulcanization reaction temperature is 100-150°C and the time is 2-8 hours, but the most preferred temperature is 120°C for 4 hours.
[0017] In step (4), the concentration of hexamethylenetetramine is 2 to 10 g / L, but the most preferred concentration is 3.5 g / L. The mass ratio of hexamethylenetetramine to cerium nitrate hexahydrate is 1:(0.25 to 4), but the optimal ratio is 1:1.
[0018] In summary, the CeO2-modified multilayer shell-like Fe-CoS nanosheet array of the present invention has the following beneficial effects:
[0019] (1) The raw materials required for preparing multilayer shell-shaped Fe-CoS nanosheets are low-cost and the synthesis process is simple. Fe-CoS nanosheet array materials have excellent conductivity and are rich in redox reactions. The internal structure of its multilayer shell can well adapt to the volume expansion problem in the reaction, exposing more active sites. After Fe-CoS is modified with CeO2, redox reaction sites can be increased while maintaining the overall structure and active site state of the original electrode material, thereby modulating the electronic structure, shortening the ion diffusion path, enhancing the synergistic effect of different components, and further improving the energy storage effect of the electrode material. Therefore, the material can be improved in many aspects such as specific capacitance and rate performance.
[0020] (2) The CeO2-modified multilayer Fe-CoS nanosheet array prepared in this invention exhibited high specific capacitance and rate performance in electrochemical tests. Cyclic voltammetry and galvanostatic charge-discharge curves were measured using a CHI 660E electrochemical workstation. Cyclic voltammetry was performed at scan rates of 5, 10, 20, 30, and 50 mV / s, with a voltage range of 0–0.8 V. Galvanostatic charge-discharge was performed at current densities of 1, 2, 3, 5, and 10 A / g, with a voltage range of 0–0.4 V. At a current density of 1 A / g, the electrode material exhibited a high specific capacitance of 1490.2 C / g, and even at a current density of 10 A / g, the electrode material maintained a specific capacitance of 427.0 C / g, demonstrating good rate performance.
[0021] (3) The preparation method of the present invention is simple and effective. The construction of the CeO2 modified multilayer shell Fe-CoS nanosheet array can be easily extended to optimize or modify other metal sulfides for energy storage devices. Attached Figure Description
[0022] Figure 1 The image shown is a scanning electron microscope image of the Co-ZIF prepared in step (1) of Example 1 of this invention.
[0023] Figure 2 The image shown is a scanning electron microscope image of Fe-Co PBA prepared in step (2) of Example 1 of this invention;
[0024] Figure 3 The image shown is a scanning electron microscope image of Fe-CoS prepared in step (3) of Example 1 of this invention;
[0025] Figure 4 This is a scanning electron microscope image of Fe-CoS / CeO2 prepared in step (4) of Example 1 of the present invention;
[0026] Figure 5 This is a transmission electron microscope image of Fe-CoS / CeO2 prepared in step (4) of Example 1 of the present invention;
[0027] Figure 6 The X-ray diffraction pattern of Fe-CoS / CeO2 prepared in step (4) of Example 1 of this invention is compared with the standard card.
[0028] Figure 7 The graph shows the electrochemical performance of Fe-CoS / CeO2 prepared in step (4) of Example 1 of this invention as an electrode material in 2MKOH electrolyte solution. The left graph is the cyclic voltammetry curve at different scan rates, and the right graph is the charge-discharge curve at different current densities.
[0029] Figure 8 The specific capacitance of Fe-CoS / CeO2 prepared in step (4) of Example 1 of this invention as an electrode material in 2MKOH electrolyte solution. Detailed Implementation
[0030] The preferred embodiments of the present invention will be described in further detail below with reference to the accompanying drawings and examples.
[0031] Example 1
[0032] A CeO2-modified multilayer shell-like Fe-CoS nanosheet array and its preparation method, comprising the following steps:
[0033] (1) Dissolve 0.29 g of cobalt nitrate hexahydrate and 0.65 g of 2-methylimidazole in 40 mL of deionized water to obtain a reaction solution. Place the cleaned nickel foam in the reaction solution and react at room temperature for 4 hours. After washing with distilled water, dry it in a forced-air drying oven to obtain Co-ZIF. Its scanning electron microscope image is shown below. Figure 1 As shown, it exhibits a nanosheet morphology with a smooth surface and a certain thickness;
[0034] (2) Co-ZIF was placed in 80 mL of deionized water containing 0.4 g potassium ferrocyanide, and the ion exchange reaction was carried out at room temperature for 1 hour to obtain Fe-Co PBA nanosheet arrays. The scanning electron microscope image is shown below. Figure 2 As shown, it exhibits a rough nanosheet morphology;
[0035] (3) The Fe-Co PBA nanosheet array was placed in 40 mL of anhydrous ethanol solution containing 0.12 g of thioacetamide and subjected to a sulfurization reaction at 120 °C for 4 hours to obtain a multilayer shell-like Fe-CoS nanosheet array. Its scanning electron microscope image is shown below. Figure 3 As shown, the morphology of the nanosheets remains intact;
[0036] (4) Dissolve 0.14 g of hexamethylenetetramine and 0.14 g of cerium nitrate hexahydrate in 40 mL of anhydrous ethanol solution. Then immerse the Fe-CoS nanosheet array prepared in step (3) into the above solution and react at 180 °C for 6 hours to obtain a CeO2-modified multilayer shell-like Fe-CoS nanosheet array, abbreviated as Fe-CoS / CeO2. Its scanning electron microscope image is shown below. Figure 4 As shown, it exhibits a cerium oxide-coated nanosheet structure with a noticeably rough surface; its transmission electron microscopy image is shown below. Figure 5 As shown, it exhibits a multi-layered shell nanosheet structure.
[0037] The X-ray diffraction pattern of Fe-CoS / CeO2 obtained by the above steps is as follows: Figure 6 As shown, the diffraction peaks belong to CeO2 (JCPDS No. 65-5923) and Co3S4 (JCPDS No. 42-1448), respectively.
[0038] Cyclic voltammetry curves at different scan rates in 2M KOH electrolyte solution, as shown below. Figure 5 As shown; the galvanostatic discharge curves at different current densities in 2M KOH electrolyte solution, as follows. Figure 6 As shown;
[0039] The Fe-CoS / CeO2 prepared in the above steps was used as an electrode material for a supercapacitor, and its electrochemical performance was tested in a 2M KOH electrolyte solution. Figure 7 As shown. The left figure is the cyclic voltammogram at different scan rates, and the right figure is the chronoamperometry analysis at different current densities;
[0040] The Fe-CoS / CeO2 prepared above was used as an electrode material for a supercapacitor. Its specific capacity at different current densities was tested in a 2M KOH electrolyte solution. Figure 8 As shown, Fe-CoS / CeO2 exhibits a specific capacitance of 1490.5 C / g at 1 A / g, and even at a current density of 10 A / g, the electrode material maintains a specific capacitance of 427.0 C / g. This demonstrates that modifying Fe-CoS nanosheet arrays with CeO2 significantly enhances electrochemical performance.
[0041] Example 2
[0042] (1) Dissolve 0.29g of cobalt nitrate hexahydrate and 0.65g of 2-methylimidazole in 40mL of deionized water to obtain a reaction solution. Place the cleaned nickel foam in the reaction solution and react at room temperature for 6 hours. After washing with distilled water, dry it in a forced-air drying oven to obtain Co-ZIF.
[0043] (2) Co-ZIF was placed in 80 mL of deionized water containing 0.8 g potassium ferrocyanide and ion exchange reaction was carried out at room temperature for 1 hour to obtain Fe-Co PBA nanosheet array.
[0044] (3) The Fe-Co PBA nanosheet array was placed in 40 mL of anhydrous ethanol solution containing 0.12 g of thioacetamide and subjected to a sulfurization reaction at 120 °C for 4 hours to obtain a multilayer shell Fe-CoS nanosheet array.
[0045] (4) Dissolve 0.14 g hexamethylenetetramine and 0.14 g cerium nitrate hexahydrate in 40 mL of anhydrous ethanol solution, and then immerse the Fe-CoS nanosheet array prepared in step (3) into the above solution and react at 180 °C for 10 hours to obtain a CeO2 modified multilayer shell Fe-CoS nanosheet array, abbreviated as Fe-CoS / CeO2.
[0046] The Fe-CoS / CeO2 prepared above was used as the electrode material of a supercapacitor. Its specific capacity at different current densities was tested in 2M KOH electrolyte solution. Fe-CoS / CeO2 had a specific capacity of 1322.5 C / g at 1 A / g.
[0047] Example 3
[0048] (1) Dissolve 0.29g cobalt nitrate hexahydrate and 1.31g 2-methylimidazole in 40mL of deionized water to obtain a reaction solution. Place the cleaned nickel foam in the reaction solution and react at room temperature for 10 hours. After washing with distilled water, dry it in a forced-air drying oven to obtain Co-ZIF.
[0049] (2) Co-ZIF was placed in 80 mL of deionized water containing 0.8 g potassium ferrocyanide and the ion exchange reaction was carried out at room temperature for 2 hours to obtain Fe-Co PBA nanosheet array.
[0050] (3) The Fe-Co PBA nanosheet array was placed in 40 mL of anhydrous ethanol solution containing 0.12 g of thioacetamide and subjected to a sulfurization reaction at 100 °C for 6 hours to obtain a multilayer shell-like Fe-CoS nanosheet array.
[0051] (4) Dissolve 0.14 g hexamethylenetetramine and 0.14 g cerium nitrate hexahydrate in 40 mL of anhydrous ethanol solution, and then immerse the Fe-CoS nanosheet array prepared in step (3) into the above solution and react at 180 °C for 10 hours to obtain a CeO2 modified multilayer shell Fe-CoS nanosheet array, abbreviated as Fe-CoS / CeO2.
[0052] The Fe-CoS / CeO2 prepared above was used as the electrode material of a supercapacitor. Its specific capacity at different current densities was tested in a 2M KOH electrolyte solution. Fe-CoS / CeO2 had a specific capacity of 1411.1 C / g at 1 A / g.
[0053] Example 4
[0054] (1) Dissolve 0.29g of cobalt nitrate hexahydrate and 0.65g of 2-methylimidazole in 40mL of deionized water to obtain a reaction solution. Place the cleaned nickel foam in the reaction solution and react at room temperature for 4 hours. After washing with distilled water, dry it in a forced-air drying oven to obtain Co-ZIF.
[0055] (2) Co-ZIF was placed in 80 mL of deionized water containing 0.4 g potassium ferrocyanide and the ion exchange reaction was carried out at room temperature for 2 hours to obtain Fe-Co PBA nanosheet array.
[0056] (3) The Fe-Co PBA nanosheet array was placed in 40 mL of anhydrous ethanol solution containing 0.18 g of thioacetamide and subjected to a sulfurization reaction at 160 °C for 6 hours to obtain a multilayer shell-like Fe-CoS nanosheet array.
[0057] (4) Dissolve 0.14 g hexamethylenetetramine and 0.14 g cerium nitrate hexahydrate in 40 mL of anhydrous ethanol solution, and then immerse the Fe-CoS nanosheet array prepared in step (3) into the above solution and react at 180 °C for 4 hours to obtain a CeO2 modified multilayer shell Fe-CoS nanosheet array, abbreviated as Fe-CoS / CeO2.
[0058] The Fe-CoS / CeO2 prepared above was used as the electrode material of a supercapacitor. Its specific capacity at different current densities was tested in a 2M KOH electrolyte solution. Fe-CoS / CeO2 had a specific capacity of 1381.5 C / g at 1 A / g.
[0059] Example 5
[0060] (1) Dissolve 0.29g of cobalt nitrate hexahydrate and 0.65g of 2-methylimidazole in 40mL of deionized water to obtain a reaction solution. Place the cleaned nickel foam in the reaction solution and react at room temperature for 4 hours. After washing with distilled water, dry it in a forced-air drying oven to obtain Co-ZIF.
[0061] (2) Co-ZIF was placed in 80 mL of deionized water containing 0.25 g potassium ferrocyanide and ion exchange reaction was carried out at room temperature for 4 hours to obtain Fe-Co PBA nanosheet array.
[0062] (3) The Fe-Co PBA nanosheet array was placed in 40 mL of anhydrous ethanol solution containing 0.12 g of thioacetamide and subjected to a sulfurization reaction at 110 °C for 2 hours to obtain a multilayer shell Fe-CoS nanosheet array.
[0063] (4) Dissolve 0.14 g hexamethylenetetramine and 0.28 g cerium nitrate hexahydrate in 40 mL of anhydrous ethanol solution, and then immerse the Fe-CoS nanosheet array prepared in step (3) into the above solution and react at 180 °C for 6 hours to obtain a CeO2 modified multilayer shell Fe-CoS nanosheet array, abbreviated as Fe-CoS / CeO2.
[0064] The Fe-CoS / CeO2 composite material prepared above was used as the electrode material of a supercapacitor. Its specific capacity at different current densities was tested in 2MKOH electrolyte solution. Fe-CoS / CeO2 had a specific capacity of 857.5C / g at 1A / g.
[0065] The embodiments described above are detailed descriptions of the technical solutions of the present invention and should be understood as specific implementation measures of the present invention. They are not intended to summarize the present invention. Any modifications, additions, or similar substitutions made within the scope of the principles of the present invention shall fall within the scope of protection that the present invention should enjoy.
Claims
1. A method for preparing a CeO2-modified multilayer shell-like Fe-CoS nanosheet array, characterized in that, The preparation method includes the following steps: (1) Dissolve 0.29 g of cobalt nitrate hexahydrate and 0.65 g of 2-methylimidazole in 40 mL of deionized water to obtain a reaction solution. Place the cleaned nickel foam in the reaction solution and react at room temperature for 4 hours. After washing with distilled water, dry it in a forced-air drying oven to obtain Co-ZIF. (2) Co-ZIF was placed in 80 mL of deionized water containing 0.4 g potassium ferrocyanide and the ion exchange reaction was carried out at room temperature for 1 hour to obtain Fe-Co PBA nanosheet array. (3) The Fe-Co PBA nanosheet array was placed in 40 mL of anhydrous ethanol solution containing 0.12 g of thioacetamide and subjected to a sulfurization reaction at 120 °C for 4 hours to obtain a multilayer shell Fe-CoS nanosheet array. (4) Dissolve 0.14 g hexamethylenetetramine and 0.14 g cerium nitrate hexahydrate in 40 mL of anhydrous ethanol solution, and then immerse the Fe-CoS nanosheet array prepared in step (3) into the above solution and react at 180 °C for 6 hours to obtain a CeO2 modified multilayer shell Fe-CoS nanosheet array.
2. The use of the CeO2-modified multilayer shell-like Fe-CoS nanosheet array prepared by the method according to claim 1 as a supercapacitor electrode material.
Citation Information
Patent Citations
Preparation method of Co3S4 nanosheet array modified by CeO2 nanoparticles
CN112164592A
MOFs derivative PBA@Co-Ni-S composite material, and preparation method and application thereof
CN113871217A